P27kip1 Is Required for Functionally Relevant Adult Hippocampal Neurogenesis in Mice. (28th November 2016) - Hörster, Henrik; Garthe, Alexander; Walker, Tara L.; Ichwan, Muhammad; Steiner, Barbara; Khan, Muhammad Amir; lie, Dieter Chichung; Nicola, Zeina; Ramirez‐Rodriguez, Gerardo; Kempermann, Gerd
Abstract: We asked whether cell‐cycle associated protein p27kip1 might be involved in the transition of precursor cells to postmitotic maturation in adult hippocampal neurogenesis. p27kip1 was expressed throughout the dentate gyrus with a strong nuclear expression in early postmitotic, calretinin‐positive neurons and neuronally determined progenitor cells (type‐3 and some type‐2b), lower or absent expression in radial glia‐like precursor cells (type‐1) and type‐2a cells and essentially no expression in granule cells. This suggested a transitory role in late proliferative and early postmitotic phases of neurogenesis. Inconsistent with a role limited to cell cycle arrest the acute stimuli, voluntary wheel running (RUN), environmental enrichment (ENR) and kainate‐induced seizures increased p27kip1 expressing cells. Sequential short‐term combination of RUN and ENR yielded more p27kip1 cells than either stimulus alone, indicating an additive effect. In vitro, p27kip1 was lowly expressed by proliferating precursor cells but increased upon differentiation. In p27kip1−/− mice neurogenesis was reduced in vivo, whereas the number of proliferating cells was increased. Accordingly, the microdissected dentate gyrus of p27kip1−/− mice generated more colonies in the neurosphere assay and an increased number of larger spheres with the differentiation potential unchanged. In p27kip1−/− monolayer cultures, proliferation was increased and cell cycle genes were upregulated. In the Morris water maze p27kip1−/− mice learned the task but were specifically impaired in the reversal phase explainable by the decrease in adult neurogenesis. We conclude that p27kip1 is involved in the decisive step around cell‐cycle exit and plays an important role in activity‐regulated and functionally relevant adult hippocampal neurogenesis. Stem Cells 2017;35:787–799 Abstract : The cell cycle associated factor p27kip1 has multiple roles in adult hippocampal neurogenesis, including the control of cell cycle exit. A p27kip1 knockout mouse shows increased proliferation of precursor cells, but (as shown in the study) reduced net neurogenesis: p27kip1 is required for controlled cell cycle exit. The images show precursor cells in the adult murine hippocampus, labeled with the bromodeoxyuridine (BrdU) method in wildtype mice (top) and p27kip1 knockout mouse (bottom). Loss of p27kip1 results in an increase in the number of BrdU‐positive cells. Scale bar, 150 µm.